Nursing experience of emergency PCI after intravenous thrombolysis in a case of acute myocardial infarction (1例急性心肌梗死静脉溶栓的护理体会) - LI Han (李涵); HAN Jianping (韩建萍); LI Ying (李影); REN Yaxing (任亚星); CAO Wenjie (曹文杰); LI Shuyue (李淑悦); YANG Yuwei (杨雨微); WANG Jing (王晶) (中西医结合护理)
to summarize a case of acute myocardial infarction (Ami) who was treated with emergency PCI after intravenous thrombolytic therapy. During the treatment, nursing intervention was carried out for the patients with severe pain due to myocardial ischemia, to enhance the patient’s own comfort. And the implementation of patients with cardiac rehabilitation care, so as to ease the patients during the treatment of excessive reaction to improve the treatment effect. This article reviews the first aid measures and nursing measures of 1 patient with acute myocardial infarction, and summarizes the relevant nursing experience (本文总结1例急性心肌梗死(AMI)静脉溶栓患者的护理经验, 包括饮食干预、健康宣教等常规护理以及疼痛干预、溶栓治疗不同阶段的护理措施, 通过快速正确诊断、密切观察病情变化、及时治疗和精心护理, 提高AMI患者生存率和生命质量。)